REVITALISASI FUNGSI SISTEM DRAINASE BERBASIS PEMBERDAYAAN MASYARAKAT DALAM RANGKA PENGURANGAN RISIKO BANJIR KOTA PANGKALPINANG - Roby Hambali (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
The implementation of this thematic KKN is based on the objective of revitalizing the function of the Pangkalpinang City drainage system to reduce the risk of flooding that has often occurred. To be able to revitalize the function, the drainage system must be viewed as a unit of the water system, and the solution requires multidisciplinary science. Problem solving in the drainage system function revitalization program emphasizes maintenance activities that use a participatory approach with the aim of influencing community behavior so that the level of public awareness increases towards the importance of a good drainage system.Four programs (11 activities) were implemented. The implementation of KKN-Thematic with a time span of one month is not able to cover all areas and all aspects of the drainage system management in Pangkalpinang City. Therefore, revitalization of drainage system functions in Pangkalpinang City is still needed in the future to reach areas in the system that are problematic and maintain good system conditions.Future programs to revitalize the function of the drainage system are projected in the form of implementation of concepts that have been initiated in the 2015 KKN-Thematic and accommodate recommendations from the Residents' Consultation, taking into account aspects of rationality and compatibility with local government programs.